Celestial Mathematics: A Recursive Framework for the Unified Expansion of Scientific Equations - Dua, Natasha (Journal of Educational Research and Policies, 2025)
Celestial Mathematics (CelMath) proposes a novel recursive expan- sion framework for physical and mathematical sciences. Unlike traditional mathematical structures, which treat numbers, space, and energy as static entities, CelMath introduces self-replicating, fractal recursion models that evolve dynamically. This paper formalizes CelMath equations, demon- strating how they generalize known mathematical physics while reducing to classical formulations when recursive effects vanish. Applications range from quantum mechanics, general relativity to artificial intelligence and computational learning. Finally, we outline potential experimental and computational tests to validate this approach.